Pathogenesis of Pasteurella multocida in Rabbits by Intra-nasal and Intra-ocular infection - Sarhad, Al-Najjar S. (The Iraqi Journal of Veterinary Medicine, 2011)
In order to study the pathogenesis of the Pasteurella multocida in its natural rout of infection, this study was done to investigate and compare its pathogenesis after intranasal and intraocular infection.Thirty (30) rabbits were divided into three groups, the 1st group (n=12) infected with 240 CFU of Pasteurella multocida intra-nasal, the 2nd (n=12) infected with 240 CFU of P. multocida intra-ocular (eye drop), and the 3rd group (n=6) served as control negative. The animals were sacrificed if they did not die naturally at 24-48hr, 3, 6, 9, 30 day post-infection (p.i.). The results showed dullness of the animals with nasal and ocular discharge and some animals dead at 48hr and 72 hr p.i. (two animals from the 1st group and four animals from the 2nd group). The gross examination of the dead and sacrificed animals showed hemorrhage in the upper respiratory tract with fibrinous pleuropericaditis and emphysematous lung in the 1st group, while the 2nd group showed eye opacity and in some animal’s eye swelling in addition to the feature noticed in the 1st group. Pasteurella multocida was isolated from the organs of all the infected animals.The histopathological changes in the 1st group were more intense than the 2nd group and concenterated at the upper and lower respiratory tract as acute hemorrhagic treacheatis with fibrinous pneumonia , while the kidney showed hypercellularity of the glomeruli with cellular degeneration of renal tubule and lymphocytic hepatitis, also there is focal gliosis. Conclusion, intranasal infection was the effective route and the main pathological changes observed in the respiratory system characterized by fibrinous pleuropneumonia.